Assessment of Gastric Accommodation in Patients with Functional Dyspepsia by 99mTc-Pertechtenate Single Photon Emission Computed Tomography Imaging: Practical but not Widely Accepted - Amiriani, Taghi (Mol Imaging Radionucl Ther, 2015)
OBJECTIVE: Impaired gastric accommodation is one of the main symptoms in patients with functional dyspepsia. The aim of the present study was to assess gastric accommodation in patients with functional dyspepsia using single photon emission computed tomography (SPECT) imaging. METHODS: Twenty-four patients with functional dyspepsia and 50 healthy volunteers as control group were enrolled in this study. All participants were given 5 mCi 99mTc-pertechtenate intravenously, served with a low fat meal, and underwent SPECT scanning 20 minutes after the meal. RESULTS: Based on the scintigraphic data, gastric volumes were found to be significantly increased after food ingestion in both patient and control groups. We also found that while there was no significant difference between patient and control groups in terms of fasting gastric volumes, postprandial gastric volume was significantly lower in patients as compared to healthy individuals (p<0.05). CONCLUSION: Measuring gastric volume by using SPECT can be a valuable method in the detection of functional dyspepsia and in differentiation of this entity from other organic disorders.